Pengetahuan Gizi Seimbang dan Olahraga Terhadap Kenaikan Berat Badan Selama Pandemi COVID-19 pada Remaja - Sri, Sri Hidayati L; Linda, Linda Prasetyaning Widayanti (Journal of Health Education and Literacy, 2022)
Degenerative or co-morbid diseases with worst prognosis of Covid-19 include obesity and DM. Both diseases are closely related to diet and physical activity. Not only the elderly, today's teenagers also suffer from this disease, especially since lockdown policy which requires teenagers to do School From Home. This study aimed to analyze the effect of knowledge about balanced nutrition and exercise routines on weight gain in adolescents during the Covid-19 pandemic. This research is an analytical observational study with a cross-sectional approach which was carried out on students of UIN Sunan Ampel Surabaya from March to May 2022. The sample of this study was 186 respondents with simple random sampling technique. Data was collected by questionnaire distributed via google form link. Data were analyzed by logistic regression with 5% confidence level. The results of this study told there was a significant effect of knowledge about balanced nutrition on weight gain. The p value was 0.000 with the regression equation obtained was y = 0.562x. It concluded that one point of knowledge about balanced nutrition variable will reduce weight gain variable by 0.562 point. There was a significant effect of exercise routine on weight gain. The p value was 0.000 with the regression equation obtained was y = 0.664x. It concluded that one point of exercise routine variable will reduce weight gain variable by 0.664 point. Teenagers are expected to have a balanced diet and sufficient physical activity even though they are doing online school so they don't gain weight.